Gyrinus confinis LeConte 1868 - Majka, Christopher; Kenner, Rex (Zenodo, 2009)
Gyrinus confinis LeConte, 1868 Gyrinus confinis was reported from New Brunswick and Nova Scotia by Roughley (1991) and from Prince Edward Island by Majka (2008) (Fig. 9). Although Morrissette (1979) reported it from running water, Oygur and Wolfe (1991) reported that 99% of specimens came from lentic habitats. : Published as part of Majka, Christopher & Kenner, Rex, 2009, The Gyrinidae (Coleoptera) of the Maritime Provinces of Canada: new records, distribution, and faunal composition, pp. 355-372 in ZooKeys 22 (22) on page 363, DOI: 10.3897/zookeys.22.216, http://zenodo.org/record/576544 : {"references": ["LeConte JL (1868) The Gyrinidae of America, north of Mexico. Proceedings of the Academy of Natural Sciences of Philadelphia 20: 365 - 373.", "Roughley RE (1991) Family Gyrinidae: Whirligig Beetles. In: Bousquet Y (Ed) Checklist of Beetles of Canada and Alaska. Ottawa, Ontario: Agriculture Canada, publication 1861 / E: pp. 72 - 673. http: // www. canacoll. org / Coleo / Checklist / PDF files / GYRINIDAE. pdf [accessed 29 June 2009]", "Majka CG (2008) The aquatic Coleoptera of Prince Edward Island, Canada: new records and faunal composition. In: Majka CG, Klimaszewski J (Eds) Biodiversity, Biosystematics, and Ecology of Canadian Coleoptera. ZooKeys 2: 239 - 260. http: // pensoftonline. net / zookeys / index. php / journal / article / viewFile / 25 / 37 [accessed 29 June 2009]", "Morrissette R (1979) Les coleopteres Gyrinidae du Quebec. Cordulia, Supplement 8: 1 - 43.", "Oygur S, Wolfe GW (1991) Classification, distribution and phylogeny of North American (north of Mexico) species of Gyrinus Muller (Coleoptera: Gyrinidae). Bulletin of the American Museum of Natural History 207: 1 - 97."]}